Inflammatory response in serrated precursor lesions of the colon classified according to WHO entities, clinical parameters and phenotype–genotype correlation. (25th February 2016) - Rau, Tilman T; Atreya, Raja; Aust, Daniela; Baretton, Gustavo; Eck, Matthias; Erlenbach‐Wünsch, Katharina; Hartmann, Arndt; Lugli, Alessandro; Stöhr, Robert; Vieth, Michael; Wirsing, Anna M; Zlobec, Inti; et al.
Abstract: Studies on traditional serrated adenoma (TSA) and sessile serrated adenoma with dysplasia (SSA‐D) are rare due to the low frequency of these lesions, which are well defined by the latest WHO classification. However, introducing new morphological criteria such as intra‐epithelial lymphocytes (IELs) might facilitate colorectal polyp diagnoses. Additionally, the phenotype–genotype correlation needs to be updated as the terminology has repeatedly changed. This study analysed 516 polyps, consisting of 118 classical adenomas (CAD), 116 hyperplastic polyps (HPP), 179 SSAs, 41 SSA‐Ds, and 62 TSAs. The lesions were analysed in relation to the patients' clinical parameters including gender, age, localisation, and size. The inflammatory background of the polyps was quantified and BRAF and KRAS mutations as well as MLH1 and CDKN2A promoter methylation were assessed. In multivariate analyses, an increase in IELs was an independent and robust new criterion for the diagnosis of SSA‐D ( p < 0.001). Superficial erosions and acute neutrophil granulocytes led to reactive changes potentially resembling dysplasia. KRAS and BRAF mutations were associated with CAD/TSA and HPP/SSA, respectively. However, almost half of TSAs had a BRAF mutation and were KRAS wild type. CDKN2A seems to precede MLH1 hyper‐methylation within the serrated carcinogenesis model. The genotyping of WHO‐based entities – and especially SSA – has sharpened in comparison to previously published data. TSAs can be sub‐grouped according to their mutation status. Of note, the higher number of IELs in SSA‐D reflects their close relationship to colorectal cancers with micro‐satellite instability. Therefore, IELs might represent a new diagnostic tool for SSA‐D.